American Water Works Association, American Society of Civil Engineers. (New York, 1998)
You can turn to the new edition of this classic reference for guidance on modernizing existing water treatment plants and planning new ones. Now with 70% new material, the Third Edition enables you to learn from 15 new chapters on environmental impact and project permitting; process residuals; construction costs; ion exchange; membrane processes; activated carbon processes; hydraulics; and more. You'll explore contributions by over 30 experts from the world's leading water quality management firms ... and keep up with the latest EPA standards and other codes.
Keywords: Water treatment plants,Thiết bị xử lý nước; Design and construction,Thiết kế và xây dựng